Quantum Dots — Characterization, Preparation and Usage in Biological Systems - Drbohlavova, Jana (Molecular Diversity Preservation International (MDPI), 2009)
The use of fluorescent nanoparticles as probes for bioanalytical applications is a highly promising technique because fluorescence-based techniques are very sensitive. Quantum dots (QDs) seem to show the greatest promise as labels for tagging and imaging in biological systems owing to their impressive photostability, which allow long-term observations of biomolecules. The usage of QDs in practical applications has started only recently, therefore, the research on QDs is extremely important in order to provide safe and effective biosensing materials for medicine. This review reports on the recent methods for the preparation of quantum dots, their physical and chemical properties, surface modification as well as on some interesting examples of their experimental use.